High‐Performance Bismuth‐Doped Nickel Aerogel Electrocatalyst for the Methanol Oxidation Reaction. Issue 33 (3rd June 2020) - Dubale, Amare Aregahegn; Zheng, Yuanyuan; Wang, Honglei; Hübner, René; Li, Yi; Yang, Jing; Zhang, Jiangwei; Sethi, Navpreet Kaur; He, Lanqi; Zheng, Zhikun; Liu, Wei
Abstract: Low‐cost, non‐noble‐metal electrocatalysts are required for direct methanol fuel cells, but their development has been hindered by limited activity, high onset potential, low conductivity, and poor durability. A surface electronic structure tuning strategy is presented, which involves doping of a foreign oxophilic post‐transition metal onto transition metal aerogels to achieve a non‐noble‐metal aerogel Ni97 Bi3 with unprecedented electrocatalytic activity and durability in methanol oxidation. Trace amounts of Bi are atomically dispersed on the surface of the Ni97 Bi3 aerogel, which leads to an optimum shift of the d‐band center of Ni, large compressive strain of Bi, and greatly increased conductivity of the aerogel. The electrocatalyst is endowed with abundant active sites, efficient electron and mass transfer, resistance to CO poisoning, and outstanding performance in methanol oxidation. This work sheds light on the design of high‐performance non‐noble‐metal electrocatalysts. Abstract : Bismuth doping reduces charge‐transfer resistance, creates a strained surface, and optimizes the d‐band center of porous Ni x Bi y aerogels. The optimum benefits of the amorphous structure and abundant superficial oxygenated species are realized in a Ni97 Bi3 aerogel, which demonstrates unprecedented electrocatalytic performance in methanol oxidation with both high activity and durability.